2021
DOI: 10.3390/su131810150
|View full text |Cite
|
Sign up to set email alerts
|

A Cause and Effect Model for Digital Sustainable Supply Chain Competitiveness under Uncertainties: Enhancing Digital Platform

Abstract: This study provides insights into digitalization in sustainable supply chain management by establishing a structural set of attributes with causal interrelationships among them, as well as by reporting empirical findings on successful criteria for footwear supply chain practices in Indonesia. Sustainable supply chain management and digitalization are mutual benefits. However, there are unclear cause and effect interrelationships. This study aims to critically pinpoint digitalization to approach sustainability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Findings imply that organizations should mainly emphasize on managing reverse logistics. These findings are aligned with the other studies done by Bratt et al (2021); Menon & Ravi, 2021a; Tseng et al (2021). Top management is often reluctant towards the implementation of sustainable practices.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Findings imply that organizations should mainly emphasize on managing reverse logistics. These findings are aligned with the other studies done by Bratt et al (2021); Menon & Ravi, 2021a; Tseng et al (2021). Top management is often reluctant towards the implementation of sustainable practices.…”
Section: Discussionsupporting
confidence: 92%
“…For successful implementation of SSCM, it is required to have some government aids or assistance to compete with the other competitors in the initial stages of implementation. Previous researchers (Leu et al, 2021; Tseng et al, 2021) also revealed that government support and policies play an important role for achieving sustainability goals in any organization. Additionally, huge expenses on collecting used products and lesser returns on investment demotivate the movement towards achieving goals for SSCM implementation.…”
Section: Discussionmentioning
confidence: 94%
“…It uses the preference judgment of each participant to judge and construct each participant's personal fuzzy preference relationship and uses the group preference relationship to choose the best solution. The project expert forecast method [10][11][12] is a structured decision support technology. Its purpose is to obtain relatively focused information and opinions through the independent and repeated objective judgments of multiple experts in the process of data collection [11].…”
Section: The Theory Of Fuzzy Delphi Methodsmentioning
confidence: 99%
“…The anonymous feedback process makes group decision-making more accurate, and can eliminate errors and improve accuracy at the same time. (3) The statistical group response can include the opinions of all individual interviewees [12]. The fuzzy Delphi method uses statistical analysis and fuzzy calculation to transform the subjective opinions of experts into quasi-objective data.…”
Section: The Theory Of Fuzzy Delphi Methodsmentioning
confidence: 99%
“…Cause-and-effect analysis is highly applicable to most fields in the industry, which is intuitive; nonetheless, examples of applicability are provided. For example, it was shown that a cause-and-effect analysis is beneficial in sustainable supply chain competitiveness [19]. In addition, transportation safety management is one the fields in which cause-and-effect analysis is highly used [20].…”
Section: The Analysis Phasementioning
confidence: 99%